HOW TO MAKE AGRICULTURE PRODUCTION IN PROTECTIVE AREAS PROFITABLE?- PROJECT IDEA ON THE EXAMPLE OF REPUBLIC OF CROATIA - Golja, Tea; Dolenc, Sanja; Marinkovic, Vladimir (Economics of Agriculture, 2012)
Agriculture has a significant impact on many economic activities. Its development is very important for every economy. Modern lifestyles as well as the increasing recognition of the value of sustainable development had influenced organic farming which importance has risen on the market as a significant and sustainable in the long-run. The subject of this paper is farming in protected areas in the Republic of Croatia. The same is achieved by conducted empirical research on shopping centres in Istria (primary research) and specific systematization and analysis of data from secondary sources. This has also proven the fundamental hypothesis that in the long run the agricultural situation in the Republic of Croatia is unsustainable due to the fact that too small and fragmented farms with inadequate institutional structure cannot be competitive and survive on the market. The goal of the paper was achieved by presenting proposals and arguments to improve the conceptual design of the present state in Croatia through the OTN Company, with special emphasis on production in protected areas.